The policy and practice of sustainable biofuels: between global frameworks and local heterogeneity the case of food security in Mozambique - Schut, Marc; Florin, M.J. (Elsevier, 2015)
This study explores the relationship between different biofuel production systems, the context in which they operate, and the extent to which various types of frameworks and schemes are able to monitor and promote their sustainability. The paper refers to the European Union Renewable Energy Directive and two international certification schemes (Roundtable on Sustainable Biofuels and NTA 8080/81) that can provide a ‘licence to sell’ biofuels on the EU market, and to the Mozambican policy framework for sustainable biofuels that provides a ‘licence to produce’ biomass for biofuels in Mozambique. Food security is used as a case study, and the food security impacts of two agro-industrial and two smallholder biofuel projects in Mozambique are described and analysed. The sustainability frameworks and schemes used in this study are able to address some, but not all, of the heterogeneity between and within different biofuel production systems. The emphasis is on monitoring agro-industrial projects while smallholder projects tend to slip through the net even when their negative impacts are evident. We conclude that globally applicable sustainability principles are useful, however, they should be operationalised at local or production system levels. This approach will support balancing between global frameworks and local heterogeneity.